Circulating genomic landscape following cyclin-dependent kinase 4/6 inhibitors exposure in HR + /HER2− metastatic breast cancer: a retrospective multi-institutional Consortium analysis - Letizia Pontolillo; Andrew A. Davis; Lorenzo Gerratana; Arielle J. Medford; Judy Wang; Eleonora Nicolo’; Katherine Clifton; Marko Velimirovic; Surbhi Warrior; Emily Podany; Eleni Andreopoulou; Mara Serena Serafini; et al. (npj Breast Cancer)
Abstract Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) plus endocrine therapy (ET) are the mainstay of treatment for hormone receptor positive, HER2 negative (HR + /HER2−) metastatic breast cancer (MBC). However, disease progression is inevitable and unveiling resistance mechanisms is crucial to guide post-CDK4/6i therapeutic strategies. In this study, we retrospectively analyzed a real-world, multi-institutional cohort of patients with HR + /HER2- MBC characterized by circulating tumor DNA (ctDNA) through next-generation sequencing (NGS) before starting second-line treatment. Among 93 patients previously treated with CDK4/6i, PIK3CA (37.6%), ESR1 (46.2%) and TP53 (31.2%) were the most altered genes. Comparing with a CDK4/6i plus ET naïve control cohort, ESR1 (p < 0.001) was significantly associated with first-line exposure. In multivariable analyses, PTEN alterations were independently associated with shorter progression free survival (PFS) (p = 0.008) and overall survival (OS) (p = 0.006), while TP53 (p = 0.031), CCDN1 (p = 0.003) and the ET second-line clinician’s choice (p = 0.011) impacted the OS. Moreover, a low-mutant allele frequency was correlated to longer PFS (p = 0.017) and OS (p = 0.038). These findings highlight the prognostic relevance of specific molecular alterations and support the role of genomic profiling in guiding second-line treatment decisions after CDK4/6i therapy. Prospective validation is warranted to confirm the clinical utility of this approach in HR + /HER2 − MBC.